Pengelolaan Hipertensi melalui Perubahan Gaya Hidup dengan Pendekatan Program KESIMA di Kampung Cikoneng, Kabupaten Bogor - Maulana, Ilham; Irawan, Olgi; Oktaviona, Nur Dita Dwi; Palupi, Amelia Destiana; Zahra, Lulu El; Rahmadanty, Shovy Dewi; Safitri, Wulan Caesar; Nirmalarani, Yayie (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Hypertension is high blood pressure with systolic pressure ≥140 mmHg and diastolic pressure ≥90 mmHg. In the working area of ​​Puraseda Health Center, Bogor Regency, there are 1,662 hypertension sufferers (Bogor Regency Health Profile). Utilization of family medicinal plants, such as making infused water, is one solution to reduce blood pressure. In addition, a balanced nutritional diet is also important in preventing hypertension. To overcome this problem, education and training on hypertension management were carried out in Cikoneng Village, Puraseda Village. This program aims to increase public awareness of the importance of a healthy diet with an approach that is easy to apply and in accordance with local wisdom. The method used is service learning with stages of preparation, implementation, coercion, and evaluation (pre-test and post-test). The results of the activity showed a significant increase in public knowledge, with an average pre-test score of 60.61 and an average increase of 25.15 points after counseling, based on the Wilcoxon test.